IDENTITY OF PROFESSIONAL GROUPS PROVIDING PSYCHOLOGICAL HELP: A LITERATURE REVIEW - Purvlice, Baiba; Mārtinsone, Kristīne; Pipere, Anita; Bortaščenoks, Rolands (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Providing high quality mental health services is one of the key objectives for national governments declared by WHO, where professional groups providing psychological help play an important role. Confusion among the professional groups in the field poses difficulties both for the professionals and service users. The paper aims to review the studies focused on the identity of professional groups providig psychological help with a special emphasis on used methodological approaches. In the first section of the paper concepts used in the relevant studies are discussed, proposing collective professional identity as the most appropriate theoretical idea to ground the future research in the given field. The second section of this paper analyses the methodological approaches applied in mentioned studies. Collective identity of professionals is conceived by the sholars in given field as a multidimensional concept which is studied both quantitatively and qualitatively. Thus far quantitative research methods are more common, but benefits of qualitative research in the future are also stressed. The results of literature review will serve as the theoretical background for studying professional groups providing psychological help in Latvia.